2020
DOI: 10.1111/jgh.15317
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐ampullary location and size ≥10 mm are independent predictors for high‐grade superficial non‐ampullary duodenal epithelial tumors

Abstract: Background and Aim The incidence of identified superficial non‐ampullary duodenal epithelial tumors (SNADETs) has been increasing with recent advances in endoscopic diagnosis. Nevertheless, the clinical features of SNADETs with malignant potential remain unclear. The aim of the present study was to clarify the clinical characteristics of high‐grade SNADETs. Methods A total of 328 SNADETs that had been endoscopically or surgically resected between January 2013 and April 2019 were identified from an endoscopic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
(51 reference statements)
1
8
0
Order By: Relevance
“…Several studies have shown that the rate of high-grade atypia is higher in the gastric type than the intestinal type. [50][51][52][53][54][55][56] Clinical and endoscopic features of gastric-type SNADETs are summarized as a predominantly preampullary location [52][53][54][55][56] and infrequent MWM or WOS (Fig. 6a,b).…”
Section: Mucin Phenotype Of Snadetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that the rate of high-grade atypia is higher in the gastric type than the intestinal type. [50][51][52][53][54][55][56] Clinical and endoscopic features of gastric-type SNADETs are summarized as a predominantly preampullary location [52][53][54][55][56] and infrequent MWM or WOS (Fig. 6a,b).…”
Section: Mucin Phenotype Of Snadetsmentioning
confidence: 99%
“…Histopathological images of each mucin phenotype, including immunohistochemical stains, are shown in Figure 5. Several studies have shown that the rate of high‐grade atypia is higher in the gastric type than the intestinal type 50–56 . Clinical and endoscopic features of gastric‐type SNADETs are summarized as a predominantly pre‐ampullary location 52–56 and infrequent MWM or WOS (Fig.…”
Section: Mucin Phenotype Of Snadetsmentioning
confidence: 99%
“…An association has been suggested between development of gastric NADETs and presence of Brunnerʼs gland hyperplasia, gastric foveolar metaplasia, and heterotopic gastric mucosa 4 5 6 . Recent studies have shown that gastric foveolar metaplasia and heterotopic gastric mucosa are more frequently observed in mucosa adjacent to gastric than intestinal NADETs, while Brunnerʼs gland hyperplasia is commonly found irrespective of tumor phenotype 7 8 . Moreover, a significant proportion of gastric foveolar metaplasia and heterotopic gastric mucosa harbored GNAS and/or KRAS mutations, which are commonly seen in gastric NADETs, suggesting that his type of NADET in the proximal duodenum develops with metaplastic gastric epithelium as a precursor 9 ( Fig.…”
Section: Figmentioning
confidence: 99%
“…In surgically resected cases, patients with gastric NADETs had worse overall and disease-free survival than those with intestinal NADETs 4 . Several observational studies have shown that gastric NADETs have a higher proportion of high-grade dysplasia or submucosal invasive cancer than intestinal NADETs 7 8 10 11 . Moreover, among gastric NADETs, most submucosal invasive cancers manifested as small lesions measuring ≤ 10 mm 8 .…”
Section: Figmentioning
confidence: 99%
“…The mucin phenotype does not affect the endoscopic resection outcome of non-ampullary duodenal epithelial tumors Some studies have focused on the association between clinicopathological features and immunohistochemical mucin phenotypes of NADETs [12][13][14][15][16][17][18]. Those reports have shown that NADETs of the gastric phenotype have a higher malignant potential than those of the intestinal type.…”
Section: Introductionmentioning
confidence: 99%